Electrical Characterization of the Boron Trifluoride Doped Poly(3-aminoacetophenone)/p-Si Junction - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz (Wiley-Blackwell, 2010)
Electrical and interface state properties of the borontrifluoride doped poly(3-aminoacetophenone)/p-Si junction have been investigated by current-voltage and impedance spectroscopy methods. Al/p-Si/P(3)APBF(3)/Aldiode indicates a nonideal behavior with electrical parameters (n = 3.53, phi(B) = 0.82 eV, and R-s = 1.4.8 k Omega), which result from the interfacial layer, series resistance, and resistance of the organic semiconductor. The obtained barrier height value of the Al/p-Si/P(3)APBF(3)/Aldiode is higher than that of the conventional Al/p-Si (phi(B) = 0.58 eV) Schottky diode. The interface state density of the diode was of the order of 1.05 x 10(12) eV(-1) cm(-2). It is evaluated that the barrier height and interface state density values of the diode are modified using the boron trifluoride doped poly (3-aminoacetophenone) organic semiconductor. POLYM. ENG. SCI., 50:929-935, 2010. (C) 2009 Society of Plastics Engineers
Keywords: Current-Voltage Characteristics; Nonpolymeric Organic-Compound; Capacitance-Voltage; Schottky Diode; Photovoltaic Properties; Devices; Barrier; Contacts; Parameters; Frequency